2021
DOI: 10.1089/hum.2020.286
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Toxicity in Nonhuman Primates Receiving Clinically Relevant Doses of an AAV9.U7snRNA Vector Designed to Induce DMD Exon 2 Skipping

Abstract: Therapeutic exon skipping as a treatment for Duchenne muscular dystrophy (DMD) has largely concentrated on the delivery of antisense oligomers to treat out-of-frame exon deletions. Here we report on the preclinical development of an adeno-associated virus (AAV)-encapsidated viral vector containing four copies of the noncoding U7 small nuclear RNA (U7snRNA), each targeted to either the splice donor or the splice acceptor sites of DMD exon 2. We have previously shown that delivery of this vector (scAAV9.U7.ACCA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
(53 reference statements)
0
24
0
Order By: Relevance
“…No or mild toxicity was also observed by Hordeaux et al 25 in a toxicology study after intra-cisterna magna injection in non-human primates, while Gushchina et al (2021) showed no toxicity even after high doses of AAV9. 45 . Although these are encouraging data supporting the safety of AAV vectors, there are also data showing that both vectors can have toxic effects after intravenous injection in both non-human primates 19 and mice 18 .…”
Section: Discussionmentioning
confidence: 99%
“…No or mild toxicity was also observed by Hordeaux et al 25 in a toxicology study after intra-cisterna magna injection in non-human primates, while Gushchina et al (2021) showed no toxicity even after high doses of AAV9. 45 . Although these are encouraging data supporting the safety of AAV vectors, there are also data showing that both vectors can have toxic effects after intravenous injection in both non-human primates 19 and mice 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, the off-target activity of scAAV9.U7.ACCA was determined to be low. To further prepare for clinical trials, Astellas assessed the toxicity of scAAV9.U7.ACCA in nonhuman primates [ 36 ]. Male juvenile cynomolgus monkeys were treated with either 3 × 10 13 vg/kg or 8 × 10 13 vg/kg of scAAV9.U7.ACCA and assessed for toxicity at 3-month and 6-month time points.…”
Section: Exon 2 Skipping For Exon 2 Duplication—astellas Gene Therapiesmentioning
confidence: 99%
“…While all BMD patients show present but biochemically abnormal dystrophin in muscle, the gene mutations causing the abnormal dystrophin are highly variable, and the precise biochemical perturbations of the dystrophin protein similarly highly variable. The most common gene mutations in BMD are two in-frame deletions ( Δ 45– 47 [ 30% ]; Δ 45– 48 [ 20% ]) [ 10 ]. The ‘reading frame rule’ defined by the out-of-frame (inactivating) DMD gene mutations in the severe DMD, and the in-frame (residual function) DMD gene mutations in BMD is correlated with protein findings in about 75% of cases; there are many exceptions to this rule.…”
Section: Becker Muscular Dystrophy and Clinical Variabilitymentioning
confidence: 99%
“…This does not target mRNA, but pre-mRNA (like exon skipping with oligonucleotides). A single clinical trial of AAV-mediated RNA editing (scAAV9.U7.ACCA; NCT04240314) is underway for exon 2 duplications [ 30 ]. The 3 rd approach to accomplishing exon-skipping is using oligonucleotide drugs to bind to the pre-mRNA (prior to splicing) to modulate RNA splicing.…”
Section: Therapeutic Approach Of Converting Duchenne To Becker Muscular Dystrophymentioning
confidence: 99%